Present Attitude of African Youth towards Entrepreneurship Career - Saheed A. Gbadegeshin; Kavoos Mohannak (European Centre for Research, Training and Development, 2022)
It is widely known that entrepreneurship plays a crucial role within the
economy. As the African economy needs rapid development and growth, this paper
investigates the present attitude of African youth towards new business creation and
entrepreneurship. Both quantitative and qualitative research methods were used, and 204
people participated in the study. The participants were accessed via social media such as
Facebook (pages and groups), LinkedIn (groups), Twitter, and WhatsApp. The results reveal
that African youth have positive attitudes and that they are entrepreneurially active and
ready to take risks, provided that they can be self-dependent. Similarly, the results show that
entrepreneurship education is much needed to improve innovative start-ups in Africa.